2021
DOI: 10.1136/bmjresp-2021-001017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of convalescent plasma for treatment of COVID-19 in Uganda

Abstract: RationaleConvalescent plasma (CCP) has been studied as a potential therapy for COVID-19, but data on its efficacy in Africa are limited.ObjectiveIn this trial we set out to determine the efficacy of CCP for treatment of COVID-19 in Uganda.MeasurementsPatients with a positive SARS-CoV-2 reverse transcriptase (RT)-PCR test irrespective of disease severity were hospitalised and randomised to receive either COVID-19 CCP plus standard of care (SOC) or SOC alone. The primary outcome was time to viral clearance, defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 33 publications
1
44
0
Order By: Relevance
“…Three studies [ 55 , 59 , 61 ] reported time to viral clearance. Two studies assessed the efficacy of convalescent plasma versus standard of care, while one study assessed the efficacy of bamlanivimab monotherapy and bamlanivimab + etesevimab combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 55 , 59 , 61 ] reported time to viral clearance. Two studies assessed the efficacy of convalescent plasma versus standard of care, while one study assessed the efficacy of bamlanivimab monotherapy and bamlanivimab + etesevimab combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 studies including 6,631 patients reported viral clearance rates and after eliminating treatments with inadequate numbers of patients, 32 studies were considered in the NMA ( 36 , 53 , 54 , 56 , 57 , 59 , 65 , 68 , 71 , 72 , 76 , 78 , 80 , 91 , 106 , 109 , 119 , 132 , 136 , 137 , 141 , 153 , 157 166 ), of which 10 were assessed as low risk ( Supplementary Table 8 ). Treatment nodes in the network included bamlanivimab, bamlanivimab plus etesevimab, convalescent plasma, favipiravir, hydroxychloroquine, hydroxychloroquine plus azithromycin, hydroxychloroquine plus favipiravir, ivermectin, ivermectin plus doxycycline, lopinavir/ritonavir, methylprednisolone, nitazoxanide, proxalutamide, remdesivir and SOC.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the included studies, 4 studies ( 24 , 28 , 34 , 48 ) were preprinted and 28 studies ( 16 – 18 , 25 27 , 29 33 , 35 – 47 , 49 52 ) were published in peer-reviewed journals. 10 studies ( 24 , 26 , 31 , 38 , 41 , 43 , 44 , 46 , 50 , 51 ) were double-blind RCTs with placebo and 22 studies ( 16 – 18 , 25 , 27 30 , 32 37 , 39 , 40 , 42 , 45 , 47 49 , 52 ) were designed as open-label trials. All trials included patients with confirmed Covid-19 except for the RECOVERY trial ( 35 ), which included both suspected and confirmed COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%